Interleukin 1β Gene Single-Nucleotide Polymorphisms and Susceptibility to Pancreatic Neuroendocrine Tumors - Cigrovski Berković, Maja (Mary Ann Liebert, Inc., 2012)
Pancreatic neuroendocrine tumors (pNETs) are rare neoplasms with not fully understood etiology. Interleukin 1β (IL1β) plays an important role in pancreatic pathology, especially carcinogenesis, but its role in pNET development remains unknown. The aim of this study was to analyze the association between IL1β polymorphisms and susceptibility to pNETs. IL1β −511 C/T and +3954 C/T single-nucleotide polymorphisms (SNPs) were analyzed by real-time polymerase chain reaction–SNP analysis. IL1β serum values in pNET patients were also determined. Association between high-expression C/T −511 IL1β genotype and susceptibility to pNET (p=0.042) was found, especially with functional pNET (p=0.014), where it was associated with the T allele (p=0.016). Combination of genotype analyses confirmed carriers of −511/+3954 CTCT to be at risk of developing functional pNETs (p=0.006) and carriers of −511/+3954 CTCC at risk of developing nonfunctional pNETs (p=0.019). IL1β serum levels of all patients were below the limit of detection. Our results suggest IL1β involvement in pNET development, and we also found association between the IL1β −511 SNP and susceptibility to pNET, especially functional pNETs. Nonfunctional pNETs seem to have inferior prognosis when compared with functional pNETs. It is possible that they differ in tumor microenvironment and that nonfunctional tumors share similarities with adenocarcinoma. We believe that our findings will contribute to understanding of the etiology and possible novel prognostic markers for pNETs when future studies investigating the serum and tumor tissue IL1β levels are done.